ICF-Based Assessment of Functioning in Daily Clinical Practice. A Promising Direction Toward Patient-Centred Care in Patients With Low Back Pain - Ibsen, Charlotte; Maribo, Thomas; Nielsen, Claus Vinther; Hørder, Mogens; Schiøttz-Christensen, Berit (Frontiers in Rehabilitation Sciences, 2021)
Background: Patient-centred care has received increased attention in recent years. Patient-Reported Outcomes (PROs) and shared decision-making are key components of Patient-Centred care. Low back pain (LBP) is a complex symptom affected by multiple, interacting factors. Therefore, evidence strongly recommend a biopsychosocial and patient-centred approach in the assessment and management. The International Classification of Functioning, Disability and Health (ICF) provide a biopsychosocial model for describing functioning and disability. ICF is widely acknowledged, but implementation into clinical practice is lacking. To support the use of a biopsychosocial and patient-centred approach in daily clinical practice among patients with LBP we developed a practice-friendly tool based on ICF; the LBP assessment tool. Objective: To compare an ICF-based assessment facilitated by the LBP assessment tool with standard care in terms of the use of PROs and shared decision-making in order to promote patient-centred care in patients with LBP. Methods: A non-randomised controlled design was used. Eligible patients were allocated to one of two groups: the ICF group, assessed with the LBP assessment tool or the control group, assessed with a conventional LBP assessment. Primary outcome include use of PROs. Secondary outcomes include use of a graphical overview displaying the patient profile and shared decision-making. A patient evaluation questionnaire was used to collect data. Results: Seven hundred ten patients were assessed for eligibility of whom 531 were allocated to the ICF group (n=299) or the control group (n=232). A significantly higher use of PRO data (p<0.00) and the patient profile (p<0.00) was reported in favor of the ICF group. Patients in the ICF group also experienced being more involved in decision-making (p=0.01). Conclusions: This study showed that a functioning assessment, by means of the LBP assessment tool, increased use of PROs and shared decision-making when compared to a conventional LBP assessment. Additionally, this study demonstrated that routine use of ICF-based PRO data and shared decision-making promoted patient-centred care in patients with LBP. The LBP assessment tool may be a strong candidate for a user-friendly ICF-based tool with the potential to support health professionals in a shift towards a biopsychosocial and patient-centred approach to patients with LBP.